Crystalline phase induced Raman enhancement on molybdenum carbides. Issue 11 (19th April 2022) - Chen, Mengxin; Song, Chuqiao; Liang, Ce; Zhang, Bin; Sun, Yanchun; Li, Siwei; Lin, Lili; Xu, Ping
Abstract : β-Mo2 C, with a lower electron work function and a higher density of states near the Fermi level than α-MoC, affords a facilitated charge transfer and stronger Raman enhancement. Abstract : Here we demonstrate crystalline phase induced Raman enhancement on molybdenum carbide materials (β-Mo2 C and α-MoC). From all the studied target molecules (rhodamine 6G, crystal violet and methylene blue), the Raman enhancement on β-Mo2 C is 2–4 times higher than that on α-MoC. Spectroscopic and theoretical calculations reveal that β-Mo2 C has a lower electron work function and a higher density of states near the Fermi level than α-MoC, which promotes the charge transfer and photo induced charge transfer processes from probe molecules to the substrate.